Modified titanium alloy material and preparation method and application thereof

By constructing a coating containing tantalum and nickel nitride on the surface of nickel-titanium alloy, the problems of vascular damage, coagulation and bacterial infection risks in the nickel-titanium vascular stent after implantation are solved, and significant antibacterial and anticoagulant properties are achieved, ensuring long-term therapeutic effect.

CN119701105APending Publication Date: 2025-03-28SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921620.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing NiTi vascular stent still has vascular damage, coagulation risks and potential bacterial infection risks after implantation, and the antibacterial and anticoagulant properties are not sufficient to ensure long-term efficacy.

Method used

By constructing a coating containing tantalum and nickel nitride on the surface of the nickel-titanium alloy, an antibacterial and anticoagulant modified coating is formed using plasma immersion injection technology.

Benefits of technology

The modified titanium alloy material exhibits significant antibacterial properties in S. aureus and E. coli, while reducing platelet adhesion, promoting endothelial cell proliferation and migration, and has good anticoagulation and pro-endothelial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701105A_ABST
    Figure CN119701105A_ABST
Patent Text Reader

Abstract

The invention provides a modified titanium alloy material and a preparation method and application thereof.The modified titanium alloy material comprises titanium alloy and a coating formed on the surface of the titanium alloy, the coating comprises tantalum and nickel nitride, and the coating is obtained by conducting plasma immersion injection process treatment on the surface of the titanium alloy and applied to medical materials. According to the technical scheme, the method is stable and controllable, operation is easy, the workpiece can be modified in all directions without being limited by the shape, and the formed coating has remarkable antibacterial, anticoagulation and endothelial promotion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of medical biomaterials, in particular to a modified titanium alloy material for medical materials and the preparation and application thereof. Background Art

[0002] Cardiovascular disease is the number one killer threatening human health and is expected to cause more than 23.6 million deaths by 2030. Interventional therapy is the main method for treating cardiovascular diseases related to vascular obstruction. The main materials for manufacturing cardiovascular stents include 316L stainless steel, cobalt-chromium alloy and nickel-titanium (NiTi) alloy. Among them, nickel-titanium alloy has good biocompatibility, unique shape memory effect and superelasticity, which can significantly improve the therapeutic effect of stents, and therefore plays an indispensable role in this field.

[0003] However, the problems of vascular damage caused by stent implantation and the risk of coagulation caused by platelet activation still need to be fully resolved. In addition, clinical studies have shown that the incidence of bacterial infection in metal stents is very low, but the potential risk still exists. Once infection occurs, the result is often fatal, with a mortality rate as high as 32.5%. Therefore, the anticoagulant and antibacterial properties of nickel-titanium vascular stents must be improved to ensure their long-term efficacy.

[0004] To prevent stent coagulation, systemic heparin therapy is usually used. However, excessive and frequent use of heparin may lead to thrombocytopenia and bleeding. The interaction between the material and the blood occurs on the surface of the material, and the coagulation process is affected by factors such as the surface morphology, composition, surface tension, charge, and semiconductor properties of the material. In addition, the vascular endothelial cell layer is considered to be an ideal anticoagulant surface. Therefore, the anticoagulant properties of the stent are expected to be achieved by regulating its surface physicochemical properties and rapid endothelialization ability.

[0005] Antibiotic treatment is the gold standard for preventing infection. However, the emergence of antibiotic resistance due to improper use has brought great challenges to the existing healthcare system. There are many ways to develop antimicrobial films on scaffolds, including the use of grafted antimicrobial substances, the construction of antimicrobial hydrogel films, and the creation of antifouling surfaces. However, the development of such films often faces challenges in ensuring mechanical adhesion, biosafety, and bactericidal efficiency. Summary of the invention

[0006] In view of the problems in the prior art, the purpose of the present invention is to provide an anti-coagulation, endothelial-promoting and antibacterial modified titanium alloy material and a preparation method and application thereof.

[0007] In one aspect, the present invention provides a modified titanium alloy material, including a titanium alloy and a coating formed on the surface thereof, wherein the coating includes tantalum and nickel nitride components.

[0008] Preferably, the tantalum is formed in the coating by a plasma immersion implantation technique.

[0009] Preferably, the nickel nitride is formed by nitriding the nickel species on the surface of the titanium alloy, and preferably, the nitriding is performed by plasma immersion implantation technology.

[0010] Preferably, the tantalum is metallic tantalum or tantalum oxide.

[0011] Preferably, the coating is obtained by performing a plasma immersion injection process on the surface of the titanium alloy.

[0012] Preferably, the nickel loading in the coating is less than 10 at.%.

[0013] Preferably, the nitrogen loading in the coating is less than 10 at.%.

[0014] Preferably, the tantalum loading in the coating is less than 10 at.%.

[0015] Preferably, the titanium alloy is nickel-titanium alloy.

[0016] Preferably, the coating is obtained by sequentially performing tantalum plasma immersion injection technology and nitrogen plasma immersion injection process on the surface of the nickel-titanium alloy.

[0017] On the other hand, the present invention provides a method for preparing the above-mentioned modified titanium alloy material, comprising:

[0018] Step 1, constructing a surface containing tantalum and nickel on the titanium alloy surface;

[0019] Step 2: nitriding the surface of the titanium alloy to form a coating containing tantalum and nickel nitride.

[0020] Preferably, the method comprises: before step 1, using a pickling solution to treat and wash the surface of the titanium alloy.

[0021] On the other hand, the present invention provides the use of the modified titanium alloy material in medical materials.

[0022] The technical solution and method of the present invention is stable and controllable, simple to operate, and can modify the workpiece in all directions without being restricted by shape. The formed coating can have significant antibacterial properties against Staphylococcus aureus and Escherichia coli. At the same time, the coating can reduce platelet adhesion, promote endothelial cell proliferation, spreading and migration, and has good anticoagulant and endothelial-promoting properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Other features, objectives and advantages of the present invention will become more apparent from a reading of the detailed description of non-limiting embodiments made with reference to the following accompanying drawings.

[0024] In the following figures, NiTi represents an unmodified sample, NiTi-N represents a sample with a single nitrogen ion implantation, NiTi-Ta represents a sample with a single tantalum ion implantation, and NiTi-Ta-N represents a sample with a tantalum implantation and then a nitrogen implantation.

[0025] Figure 1 is the scanning electron microscope image of the material;

[0026] Figure 2 is the XPS total spectrum of the material surface (the horizontal axis is the binding energy);

[0027] Figure 3 N1s (A) and Ta 4f (B) high-resolution spectra of XPS on the material surface (the horizontal axis is binding energy);

[0028] Figure 4 It is the Raman spectrum of the material surface;

[0029] Figure 5 It is a test chart of ammonia species release on the surface of materials;

[0030] Figure 6 This is an electron microscope image of platelet adhesion on the material surface;

[0031] Figure 7 These are the results of the proliferation activity experiment of human umbilical vein endothelial cells on the sample surface;

[0032] Figure 8 These are the results of the human umbilical vein endothelial cell spreading experiment on the sample surface;

[0033] Fig. 9 These are the results of the migration experiment of human umbilical vein endothelial cells on the sample surface;

[0034] Fig.10 These are the results of the human umbilical vein endothelial cell-related gene expression experiment.

[0035] Fig.11 The results of the plate coating experiment of Escherichia coli and Staphylococcus aureus on the sample surface (E.coli represents Escherichia coli, and S.aureus represents Staphylococcus aureus);

[0036] Fig.12 These are scanning electron microscope images of Escherichia coli and Staphylococcus aureus on the sample surface (E. coli represents Escherichia coli, and S. aureus represents Staphylococcus aureus). DETAILED DESCRIPTION

[0037] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.

[0038] Through research, the embodiments of the present invention found that nickel nitride can interact with protons in the solution to produce ammonia, and ultimately induce bacterial death on the surface of the implant by destroying bacterial metabolism and producing nitric oxide. This provides a good guide for designing antibacterial films on the surface of vascular stents. On the other hand, ammonia plays an important physiological role in the human body, providing an available form of nitrogen required for the synthesis of DNA, RNA and proteins. In addition, ammonia is also considered to be a signal gas that can be used to regulate the activity of endothelial cells. However, the regulatory effect of ammonia generated in situ by the stent on cells has not been fully studied. Therefore, designing a robust and reliable ammonia release platform to give nickel-titanium stents selective antibacterial and anticoagulant capabilities is a very challenging but fascinating research direction in this field.

[0039] Importantly, thrombosis and infection are complex and interrelated. Bacterial toxins can cause thrombosis, and thrombosis can easily lead to bacterial adhesion, thereby enhancing biofilm formation. Despite extensive efforts, the interrelationship between infection and thrombotic complications remains unclear, leading to serious clinical challenges. An effective method for the simultaneous treatment of thrombosis and infection is urgently needed.

[0040] To this end, an embodiment of the present invention provides a modified titanium alloy material and a preparation method and application thereof. The modified titanium alloy material includes a titanium alloy and an anticoagulant, endothelial-promoting and antibacterial coating formed on the surface thereof, wherein the antibacterial coating includes tantalum and nickel nitride components.

[0041] The modified titanium alloy material of the embodiment of the present invention forms a tantalum and nitride modified coating on the surface of the titanium alloy material, wherein the tantalum exists in the form of a single substance or an oxide; and preferably, the nickel loading of the surface coating is less than 10at.%; and the nitrogen loading of the surface coating is less than 10at.%.

[0042] The method for preparing the modified titanium alloy material according to the embodiment of the present invention comprises:

[0043] Step 1, constructing a surface containing tantalum and nickel on the titanium alloy surface;

[0044] Step 2: nitriding the surface of the titanium alloy to form a coating containing tantalum and nickel nitride.

[0045] The titanium alloy is preferably a titanium nickel alloy and is preferably implanted by sequential tantalum and nitrogen plasma immersion implantation techniques.

[0046] Among them, the cathode target material used for metal injection is preferably a single metal.

[0047] Preferably, the PIII&D process parameters used include: vacuum chamber temperature of 20 to 100°C; background vacuum of 5×10-3Pa; negative high voltage of -15 to -40kV; frequency of 5 to 10Hz; pulse width of 500 to 1000μs; and injection time of 60 to 180min.

[0048] Preferably, the atomic percentage of metal injected into the material surface is 0 to 15 at.%.

[0049] Preferably, the cathode target material used for gas injection is mainly a single gas.

[0050] And preferably, when the gas is injected, the PIII&D process parameters used include: vacuum chamber temperature of 20 to 100°C; background vacuum of 5×10-3Pa; negative high voltage of -15 to -40kV; frequency of 5 to 150Hz; pulse width of 50μs; injection time of 1 to 2h; and gas flow rate of 10 to 50cm3 / min.

[0051] It is preferred that the atomic percentage of nitrogen injected into the material surface is 0 to 15 at.%.

[0052] The method further comprises the step of treating and washing the substrate with an acid solution before the plasma immersion ion implantation.

[0053] Preferably, the pickling solution is a mixed acid of nitric acid and hydrofluoric acid; and preferably, the washing step further comprises ultrasonic cleaning using acetone, ethanol and deionized water in sequence.

[0054] In addition, the embodiments of the present invention also provide applications of surface-modified titanium alloy materials in the field of biomedical materials, especially in anticoagulant, endothelial cell-promoting and antibacterial materials.

[0055] The method of the embodiment of the present invention is controllable and simple to operate. The coating formed on the surface of the modified titanium alloy sample has significant antibacterial properties against Staphylococcus aureus and Escherichia coli. At the same time, the coating can reduce platelet adhesion (anticoagulant properties) and promote endothelial cell proliferation, spreading and migration (pro-endothelial properties).

[0056] The present invention is described below with specific embodiments and comparative examples:

[0057] Among them, the titanium alloy uses nickel-titanium alloy as the substrate, the metal injection uses pure metal tantalum as the cathode, and the nitrogen gas injection uses radio frequency excited gas to provide plasma.

[0058] Tantalum metal injection is carried out using the following process parameters: background vacuum is 5×10-3Pa; negative high voltage is -15 to -40kV, pulse width is 500 to 1000μs, frequency is 5 to 10Hz, and injection time is 1 to 3 hours.

[0059] The nitrogen plasma immersion ion implantation method is carried out with the following process parameters: background vacuum degree is 5×10-3Pa; negative high voltage is -30kV, pulse width is 50μs, frequency is 100Hz, and implantation time is 1 hour.

[0060] The following describes the experimental process in detail:

[0061] 1. A nickel-titanium sheet with a diameter of 12 mm and a thickness of 1 mm was subjected to mixed acid (hydrofluoric acid: nitric acid: deionized water = 1:5:4) and ultrasonic treatment twice (5 minutes each time), and then ultrasonically cleaned with deionized water and ethanol twice, each time for 5 minutes, to obtain a nickel-titanium alloy sheet with a smooth surface. The obtained material was named NiTi;

[0062] 2. Each sample was prepared by plasma immersion implantation and deposition technology. NiTi-N represents a sample with only nitrogen ion implantation, NiTi-Ta represents a sample with only tantalum ion implantation, and NiTi-Ta-N represents a sample with tantalum implantation and then nitrogen implantation. The specific implantation parameters are shown in Table 1.

[0063] Table 1: Metal ion implantation and deposition parameters

[0064]

[0065] 3. Evaluation of the surface physical and chemical properties of materials.

[0066] like Figure 1 As shown, the SEM morphology of the samples is shown. The NiTi surface presents a relatively dense and smooth appearance with obvious processing marks. NiTi-Ta presents a gully-like topography in the SEM image. Small particles can be observed on the surface of the NiTi-N sample, presenting a gravel-like topography. For the NiTi-Ta-N sample, after the bombardment of tantalum plasma and the combination of nitrogen plasma on its surface, the resulting morphology is combined with NiTi-Ta and NiTi-N, showing a thorny morphology.

[0067] As shown in Table 2, the surface nickel content was maintained at a low level, suggesting good biosafety of the material.

[0068] Table 2: Element content of sample surface layer tested by XPS

[0069]

[0070] like Figure 2As shown, the corresponding elements can be found in the total spectrum of samples after ion implantation of metal and gas.

[0071] like Figure 3 As shown, the high-resolution spectrum of N1s on the sample surface is displayed. In the figure (A), in the NiTi-Ta-N and NiTi-N samples, the energy binding peaks at 395.9eV and 399.8eV correspond to the binding energy of TiN. In addition, the peak at 403eV is attributed to the surface chemical adsorption of nitrogen oxides. It is worth noting that the 397.7eV signal peak appearing on the surface of the Ni-Ti-Ta-N sample corresponds to the binding energy of Ni-N, indicating the presence of nickel nitride on the surface. The figure (B) shows the high-resolution XPS spectrum of Ta4f on the sample surface. The characteristic peaks observed at 27.8eV and 25.9eV on the surfaces of NiTi-Ta and NiTi-Ta-N samples are attributed to Ta2O5. The peak at 24.4eV is attributed to Ta2O 5-x , while the peak at 22.5 eV is attributed to metal Ta. According to the above analysis, the composition of the surface film of NiTi-Ta-N sample can be summarized as Ta / Ta2O5 / Ni3N.

[0072] like Figure 4 As shown in Figure 1, a 152 cm -1 、197cm -1 and 223cm -1 These Raman peaks can be attributed to nickel nitride.

[0073] Evaluation of materials for the generation of ammonia species:

[0074] Ammonia nitrogen (NHx) was determined according to the Chinese standard HJ536-2009 using the salicylic acid colorimetric method. The experimental steps are as follows: First, phosphate buffered saline (PBS) was added to the sample surface and incubated at 37°C for 12 hours. Then, the sample was transferred to a 96-well plate, and 25 μL of a mixed color developer consisting of salicylic acid and sodium tartrate, 10 μL of sodium nitrosothreonine solution (Na2[Fe(CN)5NO]-2H2O) and 10 μL of sodium hypochlorite solution were added. After standing at room temperature for 60 minutes, the absorbance was measured at a wavelength of 697 nm using an ELISA reader, and the amount of NHx released was calculated based on the standard curve.

[0075] like Figure 5As shown in , in PBS at pH = 7.4 (normal tissue pH), ammonia generation can be seen on the surface of the NiTi-Ta-N sample. In contrast, no relevant signals were detected on the surfaces of the NiTi, NiTi-N, and NiTi-Ta samples. A significant increase in ammonia species generated on the surface of the NiTi-Ta-N sample was observed in PBS at pH = 5.5 (pH associated with bacterial infection), which was attributed to the increase in proton concentration in the solution.

[0076] Evaluation of anti-platelet adhesion of materials:

[0077] Fresh whole blood from healthy rats was centrifuged at 1500 rpm for 15 minutes to obtain a platelet-rich plasma middle layer. A total of 60 μL of platelet-rich plasma was added to the surface and treated at 37°C for 30 minutes, 1 hour, and 2 hours. Subsequently, it was washed with normal saline. A 2.5% glutaraldehyde solution (Sinopharm Group, Shanghai, China) was then added to fix the sample. A series of ethanol / water solutions with different concentrations were used for the dehydration process. Subsequently, platelet images were observed using a scanning electron microscope.

[0078] like Figure 6 As shown, it can be observed that there are fewer platelets on the surface of NiTi-Ta and NiTi-Ta-N samples, and the morphology of the platelets is basically in an inactive state, in the shape of round balls. In contrast, there are more platelets on the surface of NiTi and NiTi-N samples. In addition, the morphology of these platelets is mainly activated, with extended tentacles and a more slender morphology. This shows that the surfaces of NiTi-Ta and NiTi-Ta-N samples have excellent anti-platelet adhesion and activation properties.

[0079] Biocompatibility evaluation of materials:

[0080] The material was immersed in 75% ethanol solution and placed on a shaker for shaking. The solution was changed every 30 minutes, sterilized for 2 hours and then dried for use. To evaluate the proliferation activity of cells on the surface of the material, human umbilical vein endothelial cells (HUVECs) were inoculated at a cell density of 20,000 / well, and the fluorescence intensity was tested using the alamar Blue method to reflect the cell proliferation activity, and the biocompatibility of the modified material was characterized from the cell proliferation activity.

[0081] like Figure 7 As shown, there was no significant difference in proliferation activity after 1 day of cell inoculation. After 4 and 7 days of culture, the proliferation activity of cells on the NiTi-Ta and NiTi-Ta-N surfaces was higher than that on the NiTi sample, indicating that the film has good cell compatibility and can promote the proliferation of endothelial cells.

[0082] like Figure 8As shown, the adhesion and spreading behavior of HUVEC on the surfaces of different samples at 1 hour, 4 hours and 24 hours are shown. At the beginning of the culture, it can be observed that the cells on the NiTi, NiTi-N and NiTi-Ta samples are mainly spherical, while the cells on the NiTi-Ta-N sample have begun to protrude pseudopodia and show higher levels of F-actin expression and larger cytoskeleton area. When the culture time is extended to 4 hours, the cells on the NiTi, NiTi-N and NiTi-Ta samples extend more pseudopodia, but their F-actin expression levels are relatively low. In particular, most of the cells on the NiTi-Ta-N sample have formed pseudopodia. After 24 hours of culture, it can be seen that the spreading area of ​​the cells on the NiTi-Ta-N sample is larger than that of other samples.

[0083] like Fig. 9 As shown in the figure, after 12 hours of culture, the number of cells migrating on the surface of NiTi-Ta and NiTi-Ta-N samples was slightly higher than that of NiTi samples, which may be related to the good cell compatibility of Ta elements. After 24 hours of culture, the number of cells migrating on the surface of NiTi-Ta-N samples was significantly higher than that of other groups, and the width of the blank area of ​​NiTi-Ta-N samples was narrower than that of NiTi and NiTi-N samples, indicating that the cells of the former migrated faster.

[0084] like Fig.10 As shown, the expression of NRF2, HO-1, FGF and eNOS genes in endothelial cells on the surface of the materials was evaluated, and the results were encouraging. The angiogenesis-related gene FGF was upregulated in both NiTi-Ta and NiTi-Ta-N samples, while the nitric oxide-related gene eNOS was only upregulated in the NiTi-Ta-N sample. In addition, a significant upregulation of NRF2 and HO-1 gene expression was also observed in the NiTi-Ta-N sample.

[0085] In summary, ammonia entering the cells may be a precursor for the synthesis of NO and the promotion of the NRF2 / HO-1 gene pathway, thereby improving cell survival. Ammonia is an in vivo signaling molecule that regulates gene pathways related to vitality in endothelial cells. This provides a reasonable explanation for the observed enhanced proliferation vitality and migration ability of endothelial cells on the surface of NiTiTaNi samples.

[0086] Evaluation of antibacterial properties of materials:

[0087] The material was immersed in a 75% ethanol solution and placed on a shaker. The solution was changed every 30 minutes. After sterilization for 2 hours, it was dried and used for later use. In the experiments on Escherichia coli (E.coli, ATCC25922) and Staphylococcus aureus (S.aureus, ATCC25923), the bacterial solution was adjusted to an absorbance of 0.1 at 600nm with culture medium, and then diluted ten times with TSB culture medium and then ten times with physiological saline. At this time, the bacterial density was about 106CFU / mL; the antibacterial performance of the material was characterized by the bacterial plate coating method. The bacteria were inoculated on the surface of the material at 0.06mL / cm2, 37 ℃ and cultured for 24 hours. After culture, the bacterial solution was diluted to an appropriate concentration and spread on the surface of solid TSB agar medium. After culture at 37℃ for 16-18 hours, it was taken out and photographed. In order to observe the microscopic morphology of bacteria on the material surface, the bacteria were inoculated on the material surface and cultured at 37℃ for 24 hours. The bacterial morphology was fixed with 2.5% glutaraldehyde at 4℃. After gradient dehydration (30v% alcohol, 50v% alcohol, 75v% alcohol, 90v% alcohol, 95v% alcohol, 100v%), the bacterial morphology was observed with a scanning electron microscope.

[0088] like Fig.11 As shown, the bacterial colonies on different samples are shown, indicating that the number of colonies on the NiTi-Ta-N sample is significantly lower than that on other samples. The antibacterial efficiency of the NiTi-Ta-N sample against Escherichia coli and Staphylococcus aureus is over 99%. These findings provide a new perspective on the potential of NiTi-Ta-N materials in antibacterial applications.

[0089] like Fig.12 As shown in the figure, the scanning electron microscope images show that the bacteria on the surface of NiTi, NiTi-N and NiTi-Ta samples have clear boundaries and complete morphology. In contrast, the number of bacteria on the surface of NiTi-Ta-N sample is significantly reduced, and wrinkling and rupture of bacterial membranes are observed.

[0090] In summary, the method of the embodiment of the present invention is stable and controllable, simple to operate, and can modify the workpiece in all directions without being restricted by shape. The prepared modified titanium alloy has good antibacterial properties and excellent biocompatibility.

[0091] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A modified titanium alloy material, characterized in that: The invention comprises a titanium alloy and a coating formed on the surface thereof, wherein the coating comprises tantalum and nickel nitride components.

2. The modified titanium alloy material according to claim 1, characterized in that: The tantalum is metallic tantalum or tantalum oxide.

3. The modified titanium alloy material according to claim 1, characterized in that: The coating is obtained by performing a plasma immersion injection process on the surface of the titanium alloy.

4. The modified titanium alloy material according to claim 1, characterized in that: The nickel loading in the coating is less than 10 at.%.

5. The modified titanium alloy material according to claim 1, characterized in that: The nitrogen loading in the coating is less than 10 at.%.

6. The modified titanium alloy material according to claim 1, characterized in that: The titanium alloy is nickel-titanium alloy.

7. The modified titanium alloy material according to claim 6, characterized in that: The coating is obtained by sequentially performing tantalum plasma immersion injection technology and nitrogen plasma immersion injection process on the surface of the nickel-titanium alloy.

8. The method for preparing the modified titanium alloy material according to claim 1, characterized in that: include: Step 1, constructing a surface containing tantalum and nickel on the titanium alloy surface; Step 2: nitriding the surface of the titanium alloy to form a coating containing tantalum and nickel nitride.

9. The method for preparing the modified titanium alloy material according to claim 8, characterized in that: include: Before step 1, the method further includes using a pickling solution to treat and wash the surface of the titanium alloy.

10. Use of the modified titanium alloy material according to claim 1 in medical materials.